Bifunctional crosslinking ligands for transthyretin. Issue 9 (September 2015) - Mangione, P. Patrizia; Deroo, Stéphanie; Ellmerich, Stephan; Bellotti, Vittorio; Kolstoe, Simon; Wood, Stephen P.; Robinson, Carol V.; Smith, Martin D.; Tennent, Glenys A.; Broadbridge, Robert J.; Council, Claire E.; Thurston, Joanne R.; et al.
Abstract : Wild-type and variant forms of transthyretin (TTR), a normal plasma protein, are amyloidogenic and can be deposited in the tissues as amyloid fibrils causing acquired and hereditary systemic TTR amyloidosis, a debilitating and usually fatal disease. Reduction in the abundance of amyloid fibril precursor proteins arrests amyloid deposition and halts disease progression in all forms of amyloidosis including TTR type. Our previous demonstration that circulating serum amyloid P component (SAP) is efficiently depleted by administration of a specific small molecule ligand compound, that non-covalently crosslinks pairs of SAP molecules, suggested that TTR may be also amenable to this approach. We first confirmed that chemically crosslinked human TTR is rapidly cleared from the circulation in mice. In order to crosslink pairs of TTR molecules, promote their accelerated clearance and thus therapeutically deplete plasma TTR, we prepared a range of bivalent specific ligands for the thyroxine binding sites of TTR. Non-covalently bound human TTR–ligand complexes were formed that were stable in vitro and in vivo, but they were not cleared from the plasma of mice in vivo more rapidly than native uncomplexed TTR. Therapeutic depletion of circulating TTR will require additional mechanisms.